2016
DOI: 10.1002/pmic.201500277
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of magnetic binary metal oxides nanocomposites through dopamine chemistry for highly selective enrichment of phosphopeptides

Abstract: In this work, for the first time, magnetic binary metal oxides nanocomposites which integrated Zr and Ti into one entity on an atomic scale on polydopamine coated magnetic graphene (magG/PD/(Zr-Ti)O4 ) was designed and synthesized, and applied to the enrichment of phosphopeptides. The newly prepared magG/PD/(Zr-Ti)O4 composites gathered the advantages of large surface area, superparamagnetism, biocompatibility and the enhanced affinity properties to phosphopeptides. MagG/PD/ZrO2 , magG/PD/TiO2 , as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In summary, the on‐chip magnetic SPE‐MALDI‐TOF MS system with In 2 O 3 ‐coated Fe 3 O 4 MNPs as the adsorbent led to high selectivity, good reusability, and low detection limit when used for the detection of phosphopeptides. In addition, a comparison of the present system with some reported methods employing various magnetic metal oxides revealed that the present approach provided comparable selectivity, sensitivity, rapidness, and reagent dosage [, ].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In summary, the on‐chip magnetic SPE‐MALDI‐TOF MS system with In 2 O 3 ‐coated Fe 3 O 4 MNPs as the adsorbent led to high selectivity, good reusability, and low detection limit when used for the detection of phosphopeptides. In addition, a comparison of the present system with some reported methods employing various magnetic metal oxides revealed that the present approach provided comparable selectivity, sensitivity, rapidness, and reagent dosage [, ].…”
Section: Resultsmentioning
confidence: 94%
“…In recent years, there have been various methods to enrich phosphopeptides including ion exchange chromatography, immune affinity capture, IMAC, and metal oxide affinity chromatography (MOAC) . Among these techniques, ion exchange chromatography is difficult to be used for complex biological samples because of the low efficiency and huge sample loss.…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment : Polycatecholamines have been used as a component in the enrichment of a range of biological species from biological samples for subsequent analysis. This includes the enrichment of phosphopeptides based on their strong binding to titanium (IV) ions, hafnium (IV) ions, zirconium‐based metal–organic frameworks, and binary metal oxides of titanium (IV) and zirconium (IV) . Analysis has been conducted in situ using competitive binding of phosphopeptides and a fluorescent probe onto coated particles, the release of the probe stopping quenching due to close association with polydopamine and providing a fluorescent indication of phosphopeptide concentration .…”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%
“…Analysis has been conducted in situ using competitive binding of phosphopeptides and a fluorescent probe onto coated particles, the release of the probe stopping quenching due to close association with polydopamine and providing a fluorescent indication of phosphopeptide concentration . These phosphopeptide binding species were also immobilized onto magnetic composites subsequently used for magnetic solid phase extraction of the enriched of phosphopeptides for analysis using mass spectrometry . Magnetic solid phase extraction of modified polydopamine coated magnetic nanomaterials has also been used for other selective separations of glycopeptide, and histidine‐tagged proteins from complex biological samples and estrogens from aqueous solution .…”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%
“…A total of 349 phosphorylated sites corresponding to 170 phosphopeptides (66 mono‐ and 104 multiphosphopeptides) were identified from mouse brain extracts. Furthermore, our group integrated Zr and Ti into a whole ( Figure A), which was denoted as magG/PD/(Zr‐Ti)O 4 . 1436 phosphorylated sites corresponding to 622 phosphopeptides (163 mono‐ and 459 multiphosphopeptides) were identified from the identical mouse brain extracts.…”
Section: Nanomaterials In Phosphoproteomicsmentioning
confidence: 99%